Exploration of Local Microorganisms from Rumen and Their Potential to Make Silage from Agricultural Waste - Listya Purnamasari; Hari Purnomo; Hidayat Bambang Setyawan (ASEAN Journal on Science and Technology for Development, 2020)
Agricultural wastes are very diverse in type and have low nutrient values, especially in lignin and cellulose, which are difficult to digest. One way of overcoming this problem is by biological treatment using microorganisms, also known as silage. The availability of bio-activators that are both cost-efficient and easy to make further suggests that using local microorganisms may be an effective possible solution. This study focused on processing food crop waste (corn leaves) into silage using local microorganisms as the bio-activators. Research took place in the Agrotechnology Laboratory, University of Jember. The experimental design was completely randomized with four treatments: Treatment 1 (rumen), Treatment 2 (rumen + banana humps), Treatment 3 (rumen + petung bamboo shoots), and Treatment 4 (rumen + gamal leaves). The parameters tested were local microorganism quality (pH, total microbial, and organoleptic) and silage quality (nutrient composition, pH, and organoleptic). After three weeks, the organoleptic local microorganism test results in all treatments showed clear colors, an acidic aroma, small number of fungi, and normal pH (3–5). In terms of silage quality, the resulting local microorganisms could be used as a bio-activator in the silage fermentation process, with the maturity level indicated by a color change (green to brownish green), sweet and acidic aroma, softer tape and texture, and pH of 4–6. The proximate test results of this silage feed showed better nutrient content in the addition of formulations in the manufacture of local microorganisms. Petung bamboo shoots, gamal leaves, and banana humps can increase the nutrient content, mainly the protein. We therefore conclude that local microorganisms from the rumen and local materials can be used as activator materials in making silage from corn leaves with an increase in the value of waste nutrients.